EXTRACTIVE CLOUD POINT SPECTROPHOTOMETRIC DETERMINATION OF MESALAZINE USING BRILLIANT GREEN DYE - JABAR, FATMA M.; ISMAEL, SHIREEN O.; AL-SABHA, THEIA’A N. (Journal of Duhok University, 2023)
A simple and accurate cloud point-spectrophotometric method for determination of Mesalazine (MEZ) in pure form and pharmaceutical formulations is proposed. The procedure is based on the reaction of Mesalazine with brilliant green dye (BG) forming a pale-yellow ion-pair complex after extracting with Triton X-114 and measured at 361 nm. The experimental conditions for the phase separation were optimized. Beer’s law was obeyed in the range 0.3-3.5 µg mL-1 with molar absorptivity of 3.914×104 L.mol-1.cm-1, average recovery % of 100.82 and average relative standard deviation (RSD) is 0.87. The method was applied successfully for determination of MEZ in its pharmaceutical formulations